Current status of telehealth in Saudi Arabia during COVID-19 - Saeed M Alghamdi; Jaber S Alqahtani; Abdulelah M Aldhahir (Wolters Kluwer Medknow Publications, 2020)
Since the beginning of the coronavirus disease (COVID-19) pandemic, the responses of countries to emerging infectious diseases have altered dramatically, increasing the demand for health-care practitioners. Telehealth (TH) applications could have an important role in supporting public health precautions and the control of the spread of the COVID-19 pandemic. This review summarizes the existing literature on the current status of TH applications used during COVID-19 in Saudi Arabia and discusses the extent to which TH can support public health measures. TH mobile applications (e.g., Seha, Mawid, Tawakklna, Tabaud, and Tetamman) have found effective tools to facilitate delivering healthcare to persons with COVID-19, and tracking of COVID-19 patients. TH has been essential in the control of the spread of COVID-19 and has helped to flatten the growth curve in Saudi Arabia. Further research is needed to explore the impact of TH applications on the progression of COVID-19 in Saudi Arabia.